2021
DOI: 10.3390/molecules26195842
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Exposure to SDHI Fungicides Boscalid and Bixafen Induces a Mitochondrial Dysfunction in Selective Human Cell Lines

Abstract: Fungicides are used to suppress the growth of fungi for crop protection. The most widely used fungicides are succinate dehydrogenase inhibitors (SDHIs) that act by blocking succinate dehydrogenase, the complex II of the mitochondrial electron transport chain. As recent reports suggested that SDHI-fungicides could not be selective for their fungi targets, we tested the mitochondrial function of human cells (Peripheral Blood Mononuclear Cells or PBMCs, HepG2 liver cells, and BJ-fibroblasts) after exposure for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The authors suggest that the observed differential sensitivity to boscalid may have been driven by the differences in antioxidant capacity of the cell lines and the differences in mitochondrial content (e.g., hepatoma cells have very high numbers of mitochondria). This explanation was supported by the finding of higher levels of mitochondrial superoxide in HepG2 cells exposed to boscalid (d'Hose et al, 2021), and is congruent with the findings of Bénit et al (2019) showing that effects of SDH inhibitors are more pronounced in cell types that are not well equipped to counter oxidative insults, such as cells with impaired superoxide dismutase signaling resulting from defective nuclear factor erythroid 2–related factor 2 translocation.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The authors suggest that the observed differential sensitivity to boscalid may have been driven by the differences in antioxidant capacity of the cell lines and the differences in mitochondrial content (e.g., hepatoma cells have very high numbers of mitochondria). This explanation was supported by the finding of higher levels of mitochondrial superoxide in HepG2 cells exposed to boscalid (d'Hose et al, 2021), and is congruent with the findings of Bénit et al (2019) showing that effects of SDH inhibitors are more pronounced in cell types that are not well equipped to counter oxidative insults, such as cells with impaired superoxide dismutase signaling resulting from defective nuclear factor erythroid 2–related factor 2 translocation.…”
Section: Discussionsupporting
confidence: 76%
“…For example, Karakayali et al (2021) reported reduced viability for the mouse neuroblastoma cell line N2a after 24 to 48‐h exposure to boscalid (EC50 = 55.66 μM). d'Hose et al (2021) reported an increase in apoptosis in HepG2 cells exposed to 1 μM boscalid for 2 h, but not in peripheral blood mononuclear cells and BJ fibroblasts. The authors suggest that the observed differential sensitivity to boscalid may have been driven by the differences in antioxidant capacity of the cell lines and the differences in mitochondrial content (e.g., hepatoma cells have very high numbers of mitochondria).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Food and Agriculture Organization (FAO) of the United Nations [ 23 ], global pesticide usage in agriculture reached 2.7 million tons of active ingredients in 2020. Analytical methods for the detection of pesticide residues on food are indispensable for ensuring food safety at all steps, from the producers to the consumers, therefore avoiding exposure and toxic effects to humans [ 24 , 25 , 26 ]. Furthermore, the global pesticide usage causes environmental impacts, including the transformation of known pesticides into hitherto unknown agents [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carboxamide fungicides are a kind of ancient fungicides, the number of which occupies a large proportion. Bayer, BASF, Syngenta, and other companies have successively developed novel varieties of commercial amide fungicides, such as sopyrazam, fluopyram, and bixafen [ 18 , 19 , 20 ]. Sulfonamide compounds have various physiological activities and are widely used in pesticides.…”
Section: Introductionmentioning
confidence: 99%